Interaction with environment and stability of common bean genotypes in the South Centre Region of Brazil - Melo, Leonardo Cunha; Melo, Patrícia Guimarães Santos; Faria, Luis Cláudio de; Diaz, José Luiz Cabrera; Peloso, Maria Jose Del; Rava, Carlos Augustin; Costa, Joaquim Geraldo Cáprio da (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the stability and adaptability of genotypes of the common bean breeding program of Embrapa Arroz e Feijão, and to compare the methods AMMI, Lin & Binns and Eberhart & Russell. Twenty breeding lines and cultivars, belonging to the following commercial group of grain: black, carioca, pink, jalo, and pinto, were evaluated in 22 variety trials, during the rainy and dry seasons of 2002, 2003 and 2004, in the states of Santa Catarina, Paraná and São Paulo. There was low association between the methods AMMI and Lin& Binns (r = 0.39) and AMMI and Eberhart & Russell (r = 0.40); and no correlation between Lin & Binns and Eberhart & Russell. The most stable and productive genotypes commercial grains were: BRS Requinte and the breeding line CNFC 8075 for carioca type; BRS Supremo and BRS Campeiro for black type; and BRS Vereda for pink type.